Confronting the “Dark Side” of Higher Education Administration: Building Relational Capacity Among Academic Leaders - Jared Rawlings (Academic Chairpersons Conference Proceedings, 2023)
Unethical leadership exists in higher education and the purpose of this session is to present current research about “dark” organizational behavior, explain the impact of unethical leadership on populations in higher education (faculty, students), present central features of relational capacity, and model practices for academic leaders to build relational capacity.
Keywords: Relational Capacity; Incivility; Academic Leaders; Unethical Leadership; Empowering Leaders